Politik Identitas dalam Sejarah Pembentukan Negara Israel - Fitrah, Elpeni (Insignia: Journal of International Relations, 2014)
This paper discusses how the political identity becomes a motive of Israel state formation. Identitypolitics is a part of cultural politics which consisted by race, religion, ethnic and culture. TheAuthor identified identity politics as a concept or political movement which focusing into diversity.The main argument of this paper is Israel has succeed utilize its cultural identity narrative to unitethe perception of the Jewish around the world to reproduce as a historical justification as well asthe tools of politics for the sake of the embodiment of national ideals in establishing their ownnation state. Keywords: Identity Politics, Narrative, Perception, Israel